Residentes universitários da UFS : dinâmicas identitárias, esteriótipos e ambivalência - Santos, Guilherme Fernandes Melo dos (2012)
The identities are forged dynamically in daily life amid the socio-psychological and political conditions. In this work, we adopt the theoretical perspective of social psychology, which considers social identity as a part of self-enunciation related to the perception of belonging to social groups, along with emotional meanings associated with that membership. This paper examines the dynamics of content creation and identity among resident students of UFS University through two studies: the first following a script mixed with questionnaire and interview, and the second through meetings in the form of focus groups. The study I aimed at investigating how university residents processed their identity constructions and specifically to verify the identity dimension which would be more evident - the individual or collective - what is the importance of (being a resident) for said building identity; the level of satisfaction associated with social belonging; which representations residents have of their social belonging and, finally, what meta-stereotypes in relation to group membership are apprehended by residents in the university context. The results indicated the large capacity of the participants in constructing self-concept meanings for themselves on the individual dimension, rather than consideration of possible dimensions of collective identities. Little emphasis was also noticed on self formulations of survey participants regarding the identity category "resident / university resident", and this, plus low prevalence, is also little protruding between them. Moreover, for those who associate their identities to the recognition of social belonging, the level of satisfaction regarding their identities is ambivalent. We also verified that there is among the surveyed a representational framework regarding the social belonging that does not favor the production of identity linked to the group of resident students; this frame also includes the seizure of meta-stereotypes toward the group produced in the university context. The study II aimed to verify whether, in contexts where possibly belonging to the social group of university residents structures political positions, participants turn to the social belonging "university resident" with a higher prevalence in the promotion and projection of their statements. The results indicated that, in specific situations, university residents now use the social category to which they belong in their identity constructions with the goal of legitimizing the demands and garner resources (material and symbolic) for the group. The recognition of social contexts in which the identity dynamics are processed, the perception of stereotypes and discrimination that arise from the establishment of an undervalued social identity causes individuals not to edit their identity belongings, whereas in times of struggles for better conditions for group membership, the affirmation of social identity is needed in legitimizing the claims related to the well being of the group.